Outcomes and Prognostic Factors of Salvage Radiation for Postoperative Lymph Node Recurrence of Esophageal Squamous Cell Carcinoma - Zhang, Chi; Ge, Xiao-Lin; Huang, Chen-Jun; Zhang, Shu; Sun, Xin-Chen (Frontiers in Oncology, 2021)
Purpose: Recurrence of esophageal squamous cell carcinoma (ESCC) in regional lymph nodes (LNs) after surgical section can be treated with salvage resection, radiotherapy (RT) or chemoradiotherapy (CRT). RT or CRT is more widely used in clinic. This paper investigates the effects, toxicities and prognostic risk factors of salvage RT or CRT on patients with LN recurrence. Methods: We retrospectively analyzed the clinical outcomes of 103 patients receiving salvage RT or CRT for LN recurrence after ESCC resection. In total, 39 patients received RT alone and 64 received concurrent CRT. All the patients received intensity modulated radiation therapy (IMRT), administered with a median dose of 62 Gy (range, 50–70 Gy). Results: The median follow-up time was 44.5 months, and median survival was 22.5 months (5.5–99.5 months). One-, 3-, and 5-year overall survival (OS) were 80.6, 37.0, and 25.8%, respectively. One- and 2-year progression free survival (PFS) were 57.3 and 34.0%, respectively. Grade 3 or above toxicity was low (16.5%) and no treatment-related deaths occurred. In univariate analysis of OS, pN0 (p = 0.039), smaller LN volume (≤25 cm3, p = 0.019), combined chemotherapy (p = 0.041) and single LN recurrence (p = 0.001) were associated with prolonged OS. And pT1-2 (p = 0.044), pN0 (p = 0.042), irradiation dose (>60 Gy, p = 0.044), combined chemotherapy (p = 0.019) and single LN recurrence (p = 0.002) were associated with prolonged PFS. In multivariate analysis, the patients with only one recurrent node had a significant better OS (HR = 0.556, 95% CI 0.324–0.956, p = 0.034) and PFS (HR = 0.528, 95% CI 0.339–0.847, p = 0.008). Conclusions: Salvage RT or CRT for regional LN recurrence is effective and acceptable. Fewer recurrent nodes may indicate a better long-term survival.